Moderate Quarter Life Crisis Dominates Emerging Adult Students: Krisis Seperempat Kehidupan Moderat Mendominasi Mahasiswa Dewasa Muda - Syifa Aysah Dinda Abrori; Effy Wardati Maryam (Academia Open, 2025)
General Background: Quarter Life Crisis represents an emotional crisis commonly experienced during emerging adulthood, characterized by anxiety, self-doubt, and uncertainty regarding identity, career, and interpersonal relationships. This phenomenon is particularly salient among university students transitioning from adolescence to early adulthood. Specific Background: Prior studies have documented the prevalence of Quarter Life Crisis among early adults; however, descriptive evidence detailing categorical levels and gender-based distribution remains limited. Knowledge Gap: Existing research has not comprehensively described the frequency distribution of Quarter Life Crisis categories across demographic characteristics, particularly sex, nor provided detailed statistical profiling within a large student sample. Aims: This study aimed to describe the level of Quarter Life Crisis among undergraduate students aged 18–25 years at Universitas Muhammadiyah Sidoarjo. Results: Using a quantitative descriptive design with stratified random sampling (n = 368) and a 21-item Quarter Life Crisis Scale (α = 0.92), findings revealed that 75.543% of students were categorized at a moderate level, 13.315% at a high level, and 11.141% at a low level. Both male and female students were predominantly classified in the moderate category, although total scores were slightly higher among females. Novelty: This study provides a detailed categorical and demographic breakdown of Quarter Life Crisis levels within a balanced gender sample using JASP-based descriptive statistics. Implications: The predominance of moderate levels indicates the need for preventive psychological support and self-regulation strategies to mitigate emotional distress during emerging adulthood in higher education contexts. Highlights: The Majority of Respondents Were Classified Within the Middle-Level Category (75.543%). Female Participants Obtained Slightly Higher Cumulative Scores Than Males. A Smaller Proportion Exhibited Elevated Conditions (13.315%) Compared With Lower-Level Classification (11.141%). Keywords: Quarter Life Crisis, Emerging Adulthood, University Students, Descriptive Statistics, Gender Differences